Degradation of cytokinins by maize cytokinin dehydrogenase is mediated by free radicals generated by enzymatic oxidation of natural benzoxazinones - Frébortová, Jitka; Novák, Ondrej; Frébort, Ivo; Jorda, Radek (The Plant journal, 2010)
Hydroxamic acid 2,4-dihydroxy-7-methoxy-1,4-benzoxazin-one (DIMBOA) was isolated from maize phloem sap as a compound enhancing the degradation of isopentenyl adenine by maize cytokinin dehydrogenase (CKX), after oxidative conversion by either laccase or peroxidase. Laccase and peroxidase catalyze oxidative cleavage of DIMBOA to 4-nitrosoresorcinol-1-monomethyl ether (coniferron), which serves as a weak electron acceptor of CKX. The oxidation of DIMBOA and coniferron generates transitional free radicals that are used by CKX as effective electron acceptors. The function of free radicals in the CKX-catalyzed reaction was also verified with a stable free radical of 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid. Application of exogenous cytokinin to maize seedlings resulted in an enhanced benzoxazinoid content in maize phloem sap. The results indicate a new function for DIMBOA in the metabolism of the cytokinin group of plant hormones.
Keywords: Phloem; Free Radicals; benzoxaziny; Molecular Structure; lakasa; cytokininy; kukuřice setá; Cytokinins; biokatalýza; molekulární struktura; oxidace-redukce; Oxidation-Reduction; Oxidoreductases; Zea mays; oxidoreduktasy; Benzoxazines; floém; Laccase; Biocatalysis; peroxidasa; volné radikály; Peroxidase